Cassiope hypnoides D. Don 1834 - Jarvis, Charlie (Zenodo, 2007)
Andromeda hypnoides Linnaeus, Species Plantarum 1: 393. 1753. "Habitat in Alpibus Lapponicis." RCN: 3094. Lectotype (Stone & Stone in Cafferty & Jarvis in Taxon 51: 752. 2003 [2002]): [icon] "Andromeda foliis aciformibus confertis" in Linnaeus, Fl. Lapponica: 128, t. 1, f. 3. 1737. - Epitype (Stone & Stone in Cafferty & Jarvis in Taxon 51: 752. 2003 [2002]): Sweden. Torne lappmark, Jukkasjärvi s:n., Vassitjåkko, 17 Jul 1948, Melderis s.n. (BM-000576312). Current name: Cassiope hypnoides (L.) D. Don (Ericaceae). : Published as part of Jarvis, Charlie, 2007, Chapter 7: Linnaean Plant Names and their Types (part A), pp. 252-342 in Order out of Chaos. Linnaean Plant Types and their Types, London :Linnaean Society of London in association with the Natural History Museum on page 290, DOI: 10.5281/zenodo.291971